Gluten-free diet influence on the way of life of children with celiac disease - Stojanović-Jovanović Biljana; Đonović Nela; Vuletić Biljana (Association of Nurses Technicians and Midwives, 2018)
Celiac disease is an autoimmune disease, which occurs due to inadequate immune response in genetically predisposed individuals in contact with gluten contained in wheat, rye, barley and oats. Removing gluten from the nutrition can be a difficult task, because wheat and other grains that contain gluten are widely used in people's daily nutrition, across the world By this paper we want to evaluate the available literature, and make a review of gluten-free diet effect on the way of life of children with celiac disease Following aspects such as cross-contamination with grains containing gluten, high prices, low availability of gluten-free products and improper labeling of food can jeopardize the treatment ie. respect of gluten free diet. Survey of literature indicates that the gluten-free diet brings a lot of social compromise in the lives of children and families who have a member with this problem in the daily life of the organization. The high incidence of psychological problems such as anxiety, depression, fears, feelings of sadness and low tolerance for frustration was observed in children with celiac disease. For better and healthier life of patients with celiac disease, the constant supervision over the production and trade of gluten-free products is needed. In addition to the aforementioned, continuous education of health workers, pharmacists, caterers, hoteliers and traders about the disease. is. required as well as a broader social activity and greater involvement of social institutions.